2012
DOI: 10.1111/odi.12011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender and stress on the volatile sulfur compounds and stress biomarkers production

Abstract: Thus, the results showed that VRSCWT induced acute stress, which increased VSC production, and these effects were shown to be influenced by the gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…In previous work by our group, it was found that anxiogenic experimental situations [13, 14] and academic exams [15] resulted in increased VSCs production in healthy undergraduate students. Other studies have also reported that academic stress impaired oral health, with academic exams being implicated in plaque accumulation and gingival inflammation [34, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work by our group, it was found that anxiogenic experimental situations [13, 14] and academic exams [15] resulted in increased VSCs production in healthy undergraduate students. Other studies have also reported that academic stress impaired oral health, with academic exams being implicated in plaque accumulation and gingival inflammation [34, 38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that anxiogenic experimental situations [13, 14] and academic examinations [15] can lead to increased oral H 2 S production in healthy subjects, demonstrating a positive influence of anxiety and psychological stress on oral VSCs emanation. In these cases, the VSCs production may not necessarily be considered halitosis, but when associated with other factors, such as poor oral hygiene or periodontal diseases, increased production of these compounds may cause halitosis.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Secretory immunoglobulin A (sIgA) (dominant antibody in saliva) has also been reported to be a biomarker of stress in several studies and has been shown to be increased under mental stress conditions [4,7,11].…”
Section: Immunoglobulinmentioning
confidence: 99%
“…Cortisol, Immunoglo bulin A, Heart rate, Systolic blood pressure Job [24] To investigate the influence of chewing time on salivary stress markers Cortisol, Alphaamylase Behaviors (chewing) [11] to evaluate the influence of stress and gender on the production of volatile sulfur compounds (VSC) and salivary biomarkers.…”
Section: Cortisolmentioning
confidence: 99%
See 1 more Smart Citation